Efficacy of Apatinib Combined with Etoposide for Maintenance Therapy in Extensive Stage Small Cell Lung Cancer - Zhang, Haili; Dong, Guilan; lv, Lili (Nepalese Journal of Cancer, 2024)
Objective: To investigate the efficacy, safety and survival of apatinib combined with etoposide for maintenance therapy in extensive stage small cell lung cancer (ES-SCLC). Method: A total of 70 patients with extensive stage small cell lung cancer after standard chemo-radiotherapy who were admitted to Tangshan people’s Hospital from January 2019 to February 2023 were enrolled and then grouped into the observation group and the control group by random number table method, with 35 patients in each group. Patients from the observation group received apatinib combined with oral etoposide capsules for maintenance therapy. Patients from the control group received etoposide capsules for maintenance chemotherapy. The clinical efficacy and adverse reactions of these two groups were compared, and the 6-month and 1-year survivals were followed up. Results: The objective response rate (ORR) and disease control rate (ODC) of the observation group were higher than those of the control group [37.1% (13 / 35) vs. 17.1% (6 / 35), 65.7% (23 / 35) vs. 40% (14 / 35)], and the differences were statistically significant (all p<0.05). There was no significant difference in the incidence of adverse reactions between these two groups (p>0.05). The 6-month and 1-year survival rates of the observation group were significantly higher than those of the control group, and the differences were statistically significant (all p<0.05). Conclusion: Apatinib combined with etoposide capsules applied for maintenance therapy in extensive stage small cell lung cancer could provide improved clinical efficacy and survival rate of patients, with tolerable adverse reactions.